Does inside passing contribute to the high incidence of groin injuries in soccer? A biomechanical analysis - Dupré, T.; Funken, J.; Müller, R.; Mortensen, K. R. L.; Lysdal, F. G.; Braun, M.; Krahl, H.; Potthast, W. (Journal of Sports Sciences, 2018)
Groin injuries are common in soccer and often cause time-loss from training. While groin injuries have been linked to full effort kicking, the role of inside passing is unclear. Therefore, the purpose of this study was to investigate hip joint kinematics and muscle force, stress and contraction velocity for adductor longus and gracilis during inside passing. 3D kinematics of ten soccer players (23.4 yrs; 77.5 kg; 1.81 m) were captured with a motion capture system inside a Footbonaut. Muscle force and contraction velocity were determined with AnyBody Modelling System. Gracilis muscle forces were 9% lower compared to adductor longus (p = 0.005), but muscle stress was 183% higher in gracilis (p = 0.005). Contraction velocity reveals eccentric contraction of gracilis in the last quarter of the swing phase. Considering the combination of eccentric contraction, high muscle stress and the repetitive nature of inside passing, gracilis accumulates high loads in matches and training. These results indicate that the high incidence of groin injuries in soccer could be linked to isolated pass training. Practitioners need to be aware of the risk and refrain from sudden increases in the amount of pass training. This gives the musculoskeletal system time to adapt and might avoid career threatening injuries.